Corporate Social Responsibility and Environmental Concerns in Nigeria: A Critical Focus on Oil Producing Communities (Issues in Social and Environmental Accounting (ISEA), 2014)
A well-known fact about the Nigerian Niger Delta region is incessant conflicts between the Oil Transnational Corporations and the oil producing communities. This could be attributed to the fact that the activities of Oil TNCs have continued to unleash untold devastation on the environment of the oil producing communities and its consequences on the local economy and by extension the total obliteration of the livelihood of the inhabitants of the area. Therefore, the Oil TNCs are increasingly becoming conscious of their devastating impact on the ecology of the area and their blatant disregard for the socio-economic development of the host communities. Consequently, the Oil TNCs have come to embrace the idea of executing Corporate Social Responsibility (CSR) projects as a vehicle to intervene meaningfully in order to mitigate the adverse effects of their operations on the environments of the host communities. This paper attempts to review and analyze CSR practices of the two major Oil TNCs in Bayelsa State: Shell and Agip in six host communities: Olugboboro, Olugbobiri, Ikebiri 1, Oporoma, Angiama, and Peremabiri in Southern Ijaw local government area. The key question explored in this study is: has the practice of CSR in the Nigerian Niger Delta region by Oil TNCs brought about socio-economic development and drastic reduction in conflict between the host communities and the Oil TNCs? The paper argues that CSR projects of transnational oil corporations in Nigeria are driven by short-term expediency rather than the long term environmental developmental needs of host communities through the provision of poor quality social amenities to these communities in order to secure social license to operate. For transnational oil corporations to make positive impact in the Nigerian Niger Delta Region, their CSR projects should be long tern in nature, taking into consideration the sustainable development needs of the local communities. The CSR projects should be in the form of high quality social amenities and environmental rehabilitation and protection, which could serve the needs of the present and future generations.